Remote W.A.R.A. Compared With Face-to-Face W.A.R.A.: A Pilot Study - Weerkamp-Bartholomeus, Paula; Marazziti, Donatella; van Amelsvoort, Therese (Frontiers in Psychology, 2021)
Background Since the outbreak of the COVID-19 pandemic and its social restriction measures, online therapy is a life-saving possibility for patients with acute stress. Wiring Affect with ReAttach (W.A.R.A.) is a brief psychological intervention aiming to decrease negative affect, that can be offered online. Methods We assessed the effect of remote W.A.R.A. on negative affect in 37 patients. Consequently, we compared the effect of remote W.A.R.A. versus face-to-face W.A.R.A on negative affect in a cross-sectional design. Results W.A.R.A. remote therapy provoked a significant reduction of negative affect with a large effect size (d = 3.08, p < 0.001). However, the reduction on negative affect was smaller than with W.A.R.A. face-to-face. We found a substantial difference between W.A.R.A. remote therapy and W.A.R.A. face-to-face in decrease of negative affect (d = 1.36, p < 0.001). Limitations The major limitation of the pilot-study is the sample size of 37 patients. Besides, we designed a numeric rating scale for evaluating negative affect. We investigated the impact on negative affect by assessing “unpleasant feelings.” This conceptualization of negative affect might still be a point of discussion. Conclusion The study’s findings indicated that W.A.R.A. remote therapy significantly reduced negative affect, but to a lesser extent than W.A.R.A. face-to-face. Nevertheless, W.A.R.A. remote therapy might offer a fast relief, especially when personal contact is difficult.